2011
DOI: 10.48550/arxiv.1105.3064
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Radiation of the atomic chains exited by a channeling particle

Abstract: Basic properties of radiation of the atomic chains excited by a channeling particle are considered. Using a very simple two-dimensional model of a crystal lattice we have shown that the main part of this radiation is generated on the frequency of oscillations of a channeling particle between the crystal planes, shifted by the Doppler effect. Angular distribution of the radiation of the chain of oscillating atoms is sharply peaked in the direction of the velocity of channeling particle because of coherence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Electric field E a (t) of vibrating atoms in far zone is given by equation ( 30) in [7]. We rewrite this equation in a complex form…”
Section: Field Of the Atomic Chains Exited By A Channeling Particlementioning
confidence: 99%
See 2 more Smart Citations
“…Electric field E a (t) of vibrating atoms in far zone is given by equation ( 30) in [7]. We rewrite this equation in a complex form…”
Section: Field Of the Atomic Chains Exited By A Channeling Particlementioning
confidence: 99%
“…Assumption on radiation of this kind was expressed recently in [7]. It was shown that radiation of an atomic chain is collimated in direction of the channeling particle velocity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assumption of such radiation was expressed recently in [7]. It was shown that the basic part of radiation is generated into a cone around the direction of velocity of a relativistic channeling particle.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we study the field of oscillating atoms in detail and calculate the emission spectrum of the atomic chains, excited by a channeled particle. In section 2 we discuss some of the features of the radiation field of the atomic chains, which were not taken into account in [7]. The next section presents the calculation of the spectral and angular distribution of the radiation of the atomic chain.…”
Section: Introductionmentioning
confidence: 99%